Language of the SMO in its historical and cultural context - I. A. Izmestyeva (Вестник Самарского университета: История, педагогика, филология)
This article analyzes the language used in special military operations from a functional and semantic perspective. Nowadays, the language used by the military (the SVO as the special military operation in Ukraine) extends beyond the professional group and, thanks to media and social networks, has become understandable to most Russian speakers. The military jargon has a history dating back three hundred years, influenced by various military campaigns in which Russia and the USSR participated. The jargonisms from the early XX century, developed during the First World War, and the active development of military language in the twentieth century, are still present in modern military language. This is due to events such as the Great Patriotic War and the war in Afghanistan. Currently, there is a growing use of military terminology, alongside well-established slang terms that refer to aspects of military life, clothing, weapons, operations, orders, etc. New terms have emerged due to advancements in science and technology, as well as changes in the military-political situation. The lexemes and phrasemes used in the military sphere serve nominative, characterizing, emotional-evaluative, and gaming functions. These terms form thematic groups that make up the semantic field of military operations, based on the denotative meaning of slang words and their possible connotations. The language of the SVO reflects the historically formed and evolving military sociolect of the national language, primarily through Russian vocabulary and phraseological units, specialized terminology, and everyday slang. A small number of foreign terms, mainly related to weapons, have been adapted to fit the phonetic and grammatical rules of the Russian language. Overall, the language of the SMO used in military-political communication reflects the national and cultural characteristics of the military.